Sinus of Valsalva Aneurysm: A Rare Cause of Dyspnea. (24th August 2015) - Smer, Aiman; Elsallabi, Osama; Ayan, Mohamed; Buaisha, Haitam; Rayes, Hamza; Alshebani, Yazeid; Tantoush, Hamza; Salih, Mohsin
Abstract : Sinus of Valsalva aneurysm (SOVA) is a rare clinical entity. Clinical manifestations can vary from an incidental finding on an imaging study to a life-threatening emergency. We report a case of a 51-year-old female with a large symptomatic left SOVA. Echocardiogram and computed tomography angiography (CTA) of the chest revealed marked dilatation of the left sinus of Valsalva, measuring 7.5 cm. This resulted in superior displacement of the left main coronary artery. Surgical repair of the aneurysm with reimplantation of the right and left coronary arteries was performed in addition to aortic valve replacement (Bentall procedure). The patient had an uneventful postoperative course and remains asymptomatic at the three-month follow-up visit.